SENGKETA KEPUTUSAN TATA USAHA NEGARA PADA PENGADAAN BARANG/JASA PEMERINTAH DI KEMENTERIAN PERHUBUNGAN REPUBLIK INDONESIA - Sirajuddin Sirajuddin; Hedwig Adianto Mau; Umar Suryadi Bakry (Jurnal Ilmiah Dinamika Hukum, 2023)
The tender process at the Ministry of Transportation uses an Electronic Procurement System (SPSE) and a supporting system where the final results in the application tendered by the Selection Working Group are only in the form of Minutes of Election Results (BAHP), which are then reported to the Commitment Making Officer (PPK). to be followed up in the form of a Letter of Appointment of Goods/Services Provider (SPPBJ) whether to accept the results of the Working Group or reject it. In the process of determining this, it turned out that there was a legal debate which resulted in legal uncertainty where the Selection Working Group's determination was in the form of BAHP as the result which was used as the object of the lawsuit. Meanwhile, the opinion of the other panel of judges is inversely proportional to the BAHP issue as the object of this dispute. Apart from that, administrative efforts before filing a lawsuit were also a problem where some of the Panel of Judges passed the dismissal stage and some did not. From the results of the study it was found that the determination of the object of dispute state administrative decisions on the procurement of government goods/services, especially at the Ministry of Transportation of the Republic of Indonesia, was normatively in the basic regulations regarding Government Procurement of Goods/Services, showing the decision to determine the winner of the Working Group in the form of BAHP even though it required approval with PPK can be used as th e object of dispute in disputes over state administrative decisions. In addition, the results also show that the explanations and decisions at the State Administrative Court, the administrative e arrangements for the procurement of goods/services are objections and appeals and a guarantee of 1% (one percent). Keywords: Procurement, goods/services, administrative decision.